A Comparative study of efficacy of high dose versus low dose of suxamethonium for endotracheal intubation - Yadav, RK; Majhi, PC; Pradhan, BB (Journal of College of Medical Sciences-Nepal, 2012)
As use of suxamethonium is associated with a large number of undesirable and serious side effects, including cardiac arrhythmias and malignant hyperthermia. These undesirable effects have prompted anesthesiologists to restrict use of suxamethonium. The low dose of the drug is expected to have lower side effects without compromising its neuromuscular blocking properties as the dose dependent side effects have been known for long, so the present study carried out to compare the efficacy of high dose (1.5mg/Kg) of suxamethonium to that of low dose (0.5mg/Kg) assessed by intubation condition with neuromuscular blockade. We prospectively randomized and compared the intubating conditions with neuromuscular monitoring in 100 patients undergoing elective abdominal, gynaecological and limb surgery in CMS-TH and found duration of apnoea and time taken for recovery of twitch height was significantly shorter. Without compromising the quality of neuromuscular blockade. Suxamethonium or Succinylcholine can be used in lower doses (0.5 mg/kg) in elective cases without airway compromise to achieve intubation. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 53-57 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6812